A facile and real-time spectroscopic method for biofluid analysis in point-of-care diagnostics. (August 2013) - Kumar, Rajesh; Singh, Gajendra P; Barman, Ishan; Dingari, Narahara Chari; Nabi, Ghulam
Background: Accurate and real-time information is critical for decision making, especially in medical applications, where any delay in diagnosis due to collection, transport and storage of biofluids can have substantial ramifications for disease management.Results: We present a facile method for point-of-care biofluid diagnostics based on the spectroscopic analysis of cotton-swab contents using a Raman probe. A PCA algorithm was developed in order to understand the clustering behavior of different off-the-shelf pharmaceutical formulations based on the recorded spectral data. Furthermore, we employed the Raman probe to detect antibiotics in a human urine sample. Our observations suggest that it is possible to provide quantitative concentration determination of Raman-active analytes by using cotton swabs as a sampling probe, which offers a wealth of possibility for real-time measurement in clinical situations.Conclusion: We envision that the intrinsic simplicity of the proposed approach in conjunction with its capability for accurate analyte determination in biofluids will lead to its clinical translation and application in point-of-care settings in the near future.